On-surface synthesis of super-heptazethrene - Mishra, Shantanu; Melidonie, Jason; Eimre, Kristjan; Obermann, Sebastian; Groning, Oliver; Pignedoli, Carlo A.; Ruffieux, Pascal; Feng, Xinliang; Fasel, Roman (Chemical Communications, 2020)
Zethrenes are model diradicaloids with potential applications in spintronics and optoelectronics. Despite a rich chemistry in solution, on-surface synthesis of zethrenes has never been demonstrated. We report the on-surface synthesis of super-heptazethrene on Au(111). Scanning tunneling spectroscopy investigations reveal that super-heptazethrene exhibits an exceedingly low HOMO-LUMO gap of 230 meV and, in contrast to its open-shell singlet ground state in the solution phase and in the solid-state, likely adopts a closed-shell ground state on Au(111). This journal is
CRIS-Team Scopus Importer:2023-03-20